DISRUPTIVE INNOVATIONS: A CASE OF SOLVING HOAX INFORMATION IN INDONESIA - Tukina, Tukina; Mozin, Abd.Razak M; Sanjaya, Marta (Humaniora, 2020)
The research discussed hoax information as an effect of disruptive innovation and how to solve it in society. It applied a qualitative descriptive method with a case study focusing on hoax information of 10 million Chinese workers who came to Indonesia. The research was library research conducted through various sources of literature and journals. Data analysis was carried out by answering the points that were analyzed and cross-checked to other data sources in order to answer the research questions. It is found that living in the millennial changes rapidly; various forms of innovation are born and developed very quickly, and so do the problems and challenges. To prevent the spread of hoax information, some efforts need to be done to understand the process, ethics implementation, law enforcement, and accountability of information.